2019
DOI: 10.1109/access.2019.2929195
|View full text |Cite
|
Sign up to set email alerts
|

An Eye-Tracker-Based 3D Point-of-Gaze Estimation Method Using Head Movement

Abstract: Eye trackers are currently used to sense the positions of both the centers of the pupils and the point-of-gaze (POG) position on a screen, in keeping with the original objective for which they were designed; however, it remains difficult to measure the positions of three-dimensional (3D) POGs. This paper proposes a method for 3D gaze estimation by using head movement, pupil position data, and POGs on a screen. The method assumes that a person, usually unintentionally, moves his or her head a short distance suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Ref. [ 33 ] proposed translating the head by a short distance to find another eye gaze vector and using the crossing point of the two eye gaze vectors as the 3D POI. The constraint of the method is that users have to move their heads slightly.…”
Section: Analysis Of 3d Poimentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [ 33 ] proposed translating the head by a short distance to find another eye gaze vector and using the crossing point of the two eye gaze vectors as the 3D POI. The constraint of the method is that users have to move their heads slightly.…”
Section: Analysis Of 3d Poimentioning
confidence: 99%
“…In addition to the constant saccades of human eyes, it is found that the pupil positions sometimes disappear in the data series of pupil positions in the time domain. Therefore, the saccades and blinks of the human eye cause vibrations and outstanding peaks, respectively, as shown in Figure 4 a. W. Pichitwong and K. Chamnongthai [ 33 ] take the average to determine the representative position of the pupil and, therefore, errors occur due to pupil disappearance. If we take derivatives between consecutive time frames, the differentiation results detect peaks that represent the starting and ending points of a blink or pupil disappearance duration, as shown by ( and ) duration in Figure 4 b.…”
Section: Analysis Of 3d Poimentioning
confidence: 99%
See 1 more Smart Citation
“…1/e l 1/e f + 1/e l + 1/e r λ r = 1/e r 1/e f + 1/e l + 1/e r (5) Considering that the error between the predicted value and the actual target value in the images of the three regions will be different, we calculate the mean square error between the predicted value and the target value. As mentioned above, the regression network can predict the gaze vector by the high-quality face and eye images.…”
Section: Regression Network Architecturementioning
confidence: 99%
“…The gaze vector can be speculated from the pupil to the target's attention. It has been increasingly important as a non-verbal cue in many fields, including marketing and consumer research [1], [2], human-computer interaction [3]- [5], medical care [6]- [8], aviation and vehicle driving [9], and criminal investigation [10]- [12]. However, the existing gaze estimation systems often have the following defects: redundancy calibration process, low tolerance to head movement, limitation of lighting conditions and complex system settings, which limit the commercial promotion of gaze estimation.…”
Section: Introductionmentioning
confidence: 99%